A new cathode material of NiF2 for thermal batteries with high specific power. (20th November 2020) - Chang, Qing; Luo, Zeshunji; Fu, Licai; Zhu, Jiajun; Yang, Wulin; Li, Deyi; Zhou, Lingping
Abstract: Transition metal halides, especially fluorides, are promising candidates utilized as cathode materials for primary batteries, thanks to their attractive electrochemical properties such as high conversion potential as well as extraordinary specific capacity. The intrinsic thermal stability stemming from the characteristic ionic bond, M–F, also enables them to be applied in some severe conditions. Herein, we investigate the discharge performance of NiF2 under large current density (0.1 A cm -2, 0.2 A cm -2 and 0.5 A cm -2 ), together with extremely high temperature of 520 ℃, 550 ℃ and 580 ℃. It can exhibit excellent electrochemical properties with the maximum specific power up to 16.2 kW kg -1 at current density of 0.5 A cm -2 and temperature of 550 ℃, at cutoff voltage of 2 V (80% of the peak voltage). When the current density is controlled at 0.1 A cm -2, the specific power can also reach at 3.5 kW kg -1 with other parameters as the same. Afterwards, XRD and XPS are conducted to further evidence the discharge mechanism of this process, confirming it as NiF2 + 2Li → Ni + 2LiF. Based on them, we believe that this work will afford insights into alternatives of cathode materials in the area of high specific power thermal batteries. Graphical abstract: Image, graphical abstract